Quick Reference Guide to Citrus Insecticides and Miticides - Lauren M. Diepenbrock; Philip A. Stansly; Lukasz L. Stelinski; Jamie D. Burrow; Jawwad A. Qureshi (EDIS)
This document is a two-page quick reference guide to citrus insecticides and miticides recommended in the Florida Citrus Pest Management Guide, their effects on important citrus pests, and their natural enemies. It is a minor revision written by L. M. Diepenbrock, P. A. Stansly, L. L. Stelinski, J. D. Burrow, and J. A. Qureshi, and published by the Entomology and Nematology Department, August 2019.